The effects of a pyrrolidine functional group on the magnetic properties of N@C60 - Zhang, J; Morton, J; Sambrook, MR; Porfyrakis, K; Ardavan, A; Briggs, G (2006)

(untitled)
A new stable pyrrolidine functionalized fullerene derivative, C69H10N2O2, has been synthesized, purified by high performance liquid chromatography, and characterized by MALDI mass spectrometry, UV-vis spectroscopy, Fourier transform infrared, 1H and 13C nuclear magnetic resonance. The magnetic properties of the analogous endohedral species have been studied by both continuous wave (CW) and pulsed EPR. CW-EPR spectra indicated an anisotropic hyperfine interaction and a permanent zero-field-splitting (ZFS). Both CW and pulsed EPR showed the ZFS parameter Deff to be around 17 MHz. Pulsed EPR revealed a biexponential decay in both T1 and T2, yielding a molecular tumbling correlation time τc of 31.4 ± 2.5 ps. © 2006 Elsevier B.V. All rights reserved.